Вновь о путешествии А. Контарини, Сараях и не только... - Рудаков, В.Г. (Степи Европы в эпоху средневековья, 2012)
V.G.Rudakov's paper is a response to and refutation of I. V. Volkov's publication in the 8,h volume of the series. V.G.Rudakov points out the features of l.V. Volkov's style, which, he considers, is far from being scholarly and tactful to his opponents. The author analyses I.V.Volkov’s numerous impolite allegations concerning him and argues that they are erroneous, artificial, and often falsified. Besides, I.V.Volkov’s previous accusations are touched upon; in particular, on the basis of facts V.G.Rudakov proves that his accusations of incorrect use of the data from I. V. Volkov's paper of 2000 are groundless. A considerable part of the paper is devoted to the analysis of the evidence of the Venetian ambassador A.Contarini of the location of Saray town and some other fragments of his work “Travel to Persia”. The researcher proves that I.V. Volkov inadequately translated the Old Italian phrase into Russian, freely manipulating with meanings of words and word combinations. The author comes to a conclusion that this key phrase of Contarini contains semantic discrepancy and apparently cannot be interpreted correctly.